2019
DOI: 10.1111/mpp.12868
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling uncovers a Lilium regale NAC transcription factor, LrNAC35, contributing to defence response against cucumber mosaic virus and tobacco mosaic virus

Abstract: Summary Cucumber mosaic virus (CMV) is a highly prevalent viral pathogen causing substantial damage to the bulb and cut‐flower production of Lilium spp. Here, we performed an Illumina RNA sequencing (RNA‐Seq) study on the leaf tissues of a virus‐resistant species Lilium regale inoculated with mock control and CMV. A total of 1346 differentially expressed genes (DEGs) were identified in the leaves of L. regale upon CMV inoculation, which contained 34 up‐regulated and 40 down‐regulated DEGs that encode putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 90 publications
1
27
0
Order By: Relevance
“…The C terminus of NAC TFs normally confers a diversified transcriptional regulatory region (TRR) that attributes to its activation or repression properties (Ooka et al, 2003;Olsen et al, 2005). NAC TFs have been reported to participate in various processes, such as biotic and abiotic stress response, formation of a secondary cell wall, senescence, meristem regulation and so on (Kubo et al, 2005;Fang et al, 2008;Yamaguchi et al, 2008;Balazadeh et al, 2011;Mao et al, 2017;Li et al, 2019;Sun et al, 2019, Sakuraba et al, 2020. However, their functions in endosperm have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The C terminus of NAC TFs normally confers a diversified transcriptional regulatory region (TRR) that attributes to its activation or repression properties (Ooka et al, 2003;Olsen et al, 2005). NAC TFs have been reported to participate in various processes, such as biotic and abiotic stress response, formation of a secondary cell wall, senescence, meristem regulation and so on (Kubo et al, 2005;Fang et al, 2008;Yamaguchi et al, 2008;Balazadeh et al, 2011;Mao et al, 2017;Li et al, 2019;Sun et al, 2019, Sakuraba et al, 2020. However, their functions in endosperm have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on NAC TFs have reported that the NAC genes respond to at least one biotic or abiotic stress, such as saline-alkali, drought, cold, or exogenous abscisic acid (ABA), which play important roles in plant drought tolerance, saline-alkali tolerance, virus resistance, and the cold resistance response (Ju et al, 2020;Gao et al, 2018). In previous studies, most NAC TFs are closely related to salt and alkali tolerance, cold tolerance, and disease resistance of plants, whereas other NAC TFs improve plant resistance to multiple stressors at the same time (Sun et al, 2019;Puranik et al, 2012;Xia et al, 2010). The A. thaliana NAC TFs ATAF1, ANAC016, ANAC019, ANAC055, and ANAC072 (Tran et al, 2004;Wu et al, 2009); the O. sativa NAC TFs OsNAC045, OsNAC10, and OsNAC022 ; the G. max NAC TFs GmNAC085, GmNAC109, GmNAC30, GmNAC81, GmNAC003, GmNAC004, GmNAC11, and GmNAC20 (Nguyen et al, 2018;Yang et al, 2019;Hao et al, 2011); and the T. turgidum NAC TF TaRNAC1 (Hao et al, 2011;) enhance drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation' sequencing (NGS) technology has provided a powerful tool for the studies of emerging and re-emerging human and animal pathogens/diseases. NGS technology, including whole genome sequencing, RNA-Seq, and single cell sequencing, has been extensively applied in genome sequencing, gene expression profiling analysis, and pathogen detection ( 15 , 23 25 ).…”
Section: Introductionmentioning
confidence: 99%